O constitucionalismo como árvore viva de Wil Waluchow: entre emergência e autoritarismo - Gomes Júnior, Francisco Tarcísio Rocha (2022)
The advance of authoritarianism is a relevant issue for different people in the contemporary world. Unlike the past, coups and radical institutions were no longer important as structures of their deployment in the past. By adopting the institutional language of liberal democracy, authoritarian regimes maintain a propaganda of democratic stability while concentrating political power and imprisoning opposing leaders. Constitutional jurisdiction is at the center of this debate because of its role in the analysis of relevant political and constitutional issues in several countries. To weaken it, campaigns to demoralize public opinion are organized. In this context, the debate around the legitimacy of constitutional review emerges as technology for clarifying and controlling the performance of constitutional courts. The main goal of this thesis is to analyze Wil Waluchow’s constitutionalism as a living tree and the debate provided by him as an instrument to improve the understanding of constitutional revision in such a way as to know how to deal with the different forms of authoritarianism that exist. The methodology used was the bibliographic analysis of articles and books aimed at determining the main forms of combating authoritarianism so that they serve as guide for the interpretation of the debate around the legitimacy of the constitutional revision as well as Wil Waluchow’s proposal. The result is that living constitutionalism proposes such a Copernican turn in the conception of constitutional revision that it suggests the overcoming of the North American tradition of strong model by a weak or dialogic model in which the parliament and the courts can dialogue around the protection of the constitutional morality of the community, which represents its authentic intentions. The method suggested to guide the constitutional courts here is the common law, which is considered by Wil Waluchow as capable of assuring the resolution of concrete, predictable and unpredictable problems concerning fundamental rights, respecting the values of strictness in the orientation of conduct and flexibility in adapting to new social realities. The final considerations indicate that Waluchow’s living constitutionalism is the result of an anti-abusive interpretation, that is, it aims at preventing the strengthening of authoritarian regimes through constitutional revision. However, it is still necessary to dive deeper into the subject so that authoritarian advances over constitutional jurisdiction are satisfactorily understood and, perhaps, overturned.